Update on the surgical management of Graves’ orbitopathy - Baeg, Joonyoung; Choi, Han Sol; Kim, Charm; Kim, Hyuna; Jang, Sun Young (Frontiers in Endocrinology, 2023)
Graves’ orbitopathy (GO) is a complex autoimmune disorder of the orbit that causes the eye to appear disfigured. GO is typically associated with Graves’ disease, an inflammatory autoimmune condition that is caused by thyrotropin receptor autoantibodies. Although our knowledge of the pathophysiology of GO has improved, its exact pathogenesis remains unclear. Some patients suffer from disfigurement, double vision, and even vision loss rather than hyperthyroidism. The disease severity and activity prompt different treatments, as the signs of GO are heterogeneous, so their management can be very complex. Despite medical advances, the first-line treatment for moderate-to-severe active GO is still glucocorticoids, while surgery can be critical for the treatment of chronic inactive GO. Surgery is sometimes required in the acute phase of the disease when there is an immediate risk to vision, such as in dysthyroid optic neuropathy. Most surgeries for GO are rehabilitative and subdivided into three categories: decompression, strabismus repair, and lid surgery. This review is a basic overview of the field, with up-to-date knowledge of the surgical techniques for GO. We review and summarize recent literature on the advances in surgery for GO to provide up-to-date insights on the optimal surgical treatment for GO.